Flexible Wages and the Costs of Job Displacement - Sofia Fernández Guerrico; Ilan Tojerow (Institute of Labor Economics (IZA), 2021)
This paper investigates whether flexible pay increases the wage costs of job displacement. We use quasi-exogenous variation in the timing of job loss due to mass layoffs spanning over an institutional reform that restricted single-employer bargaining, the Belgian Wage Norm in 1996. We find that average earnings losses over a ten-year period after displacement are 10 percentage points larger under flexible pay. Workers displaced from jobs with higher employer-specific wage premiums-service sector and white-collar-benefit the most from restricted single-employer bargaining as their earnings fully converge to non-displaced workers' earnings within three years. We show that the differences in earnings losses across wage-setting systems are not driven by fluctuations in the business cycle. Finally, the wage-setting reform had similar effects on female workers, though it did not narrow the gender gap in pre-layoff wages. Our results suggest that reduced pay flexibility may help displaced workers catch up faster to non-displaced workers' pay premium ladder conditional on re-employment.
Keywords: J31; J51; J63; 330; bargaining; wage flexibility; job displacement